Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Siswa SMP Negeri 1 Gunungsitoli Alo’oa Tahun Pelajaran 2023/2024 - Dasari Waruwu; Sudiman Zendrato (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
This study was motivated by the low learning outcomes and student motivation in Science (IPA) subjects at the junior high school level. The purpose of this study was to improve the quality of learning, learning motivation, and student learning outcomes through the implementation of the Problem Based Learning (PBL) model. This research employed a Classroom Action Research (CAR) design conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 20 eighth-grade students of SMP Negeri 1 Gunungsitoli Alo’oa. Data were collected through observation, learning outcome tests, motivation questionnaires, and interviews. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed a significant improvement from cycle I to cycle II: learning quality increased from 74.25% to 82.55%, learning motivation increased from 69.79% to 86.76%, and the average learning outcomes improved from 64.33 to 79.82 with classical completeness reaching 90%. These findings indicate that the implementation of the Problem Based Learning model is effective in improving learning quality, student motivation, and science learning outcomes.